The supervision of registered social workers in Aotearoa New Zealand: A national survey - O’Donoghue, Kieran B. (Aotearoa New Zealand Social Work, 2019)
INTRODUCTION: Registered social workers in Aotearoa New Zealand are expected to participate in supervision in accordance with the Social Workers Registration Board’s policies. This article reports baseline findings on the supervision of registered social workers, comparing their supervision with the Board’s policy and guidelines. METHODS: A postal survey of 278 registered social workers was conducted to establish a baseline regarding their supervision. IBM SPSS 24 was used to analyse the data. Descriptive analysis, one-way ANOVA and post hoc tests were applied to explore variances in means for the independent variables of registration type, gender, age, ethnic identity, sexual orientation, recognised qualifications, and experience as social worker across 11 scales concerning the respondents’ supervision. FINDINGS: The findings report demographic information about the supervisees as well as a description of the supervision they participated in. This includes detail about various aspects of supervision, including forms, overall emphasis, logistics, types of contact, climate, methods and processes, experiences of their supervisor’s approaches and models, session processes and content and their overall satisfaction and evaluation. CONCLUSIONS: While most registered social workers’ supervision is in accordance with the Board’s expectations and Code of Conduct, further work is needed to ensure all registered social workers participate in appropriate supervision that meets these expectations. Concerns are raised about the cultural responsiveness of supervision in relation to supervisees and clients. Suggestions are made concerning further research in relation to the influence of gender, culture, sexual orientation, experience, qualifications, and registration status within supervision.